Parental Choice Influence in Promoting Students’ Enrolment in Physical Education in Senior Secondary Schools in Enugu State: A Survey of Sampled Experts - Omeje, Faith Chidinma; Saratu , Kabir (International Journal of Human Kinetics, Health and Education, 2023)
This study investigated parental choice influence in promoting students’ enrolment in Physical Education [PE] in Senior Secondary Schools [SSS] in Enugu State. The study adopted a cross-sectional survey research design and was conducted in Enugu State, Nigeria. A total of 58 PE experts constituted the study population and were studied. Possession of master’s degree qualification and working as academic staff in tertiary institutions qualifies an expert. A researcher-designed self-administered instrument called “Parental Choice Influence in Physical Education Questionnaire [PACIPEQ] which demonstrated .91 internal consistency Cronbach’s Alpha value was used for data collection. Mean value and standard deviation was adopted for answering research question while independent samples t-test statistics was used to test hypothesis at .05 significance. The study revealed that PE experts considered parents’ enlightenment on the need to make choices regarding subject of interest (=2.98; SD=.99), having corresponding relationship and understanding (=2.96; SD=1.04) and parents’ decisions regarding choice of subjects (=2.94; SD=1.03) as viable strategies for promoting students’ enrolment in PE in SSS. No significant difference was recorded in the parental choice influence in promoting students’ enrolment in PE in SSS based on experts’ educational qualification and years of work experience (p>.05), while difference existed on gender (p<.05). Conclusively, the experts considered parents’ enlightenment, corresponding relationship and understanding as well as parents’ decisions regarding choice of PE subject as viable strategies for promoting students’ enrolment in PE in SSS in Enugu State. Therefore, the need for accommodating parental choice in promoting students’ enrolment in PE in SSS by the school administration and PE experts regardless of socio-demographic variations becomes paramount.